2020
DOI: 10.3390/jcm9030669
|View full text |Cite
|
Sign up to set email alerts
|

3,2′-Dihydroxyflavone Improves the Proliferation and Survival of Human Pluripotent Stem Cells and Their Differentiation into Hematopoietic Progenitor Cells

Abstract: Efficient maintenance of the undifferentiated status of human pluripotent stem cells (hiPSCs) is crucial for producing cells with improved proliferation, survival and differentiation, which can be successfully used for stem cell research and therapy. Here, we generated iPSCs from healthy donor peripheral blood mononuclear cells (PBMCs) and analyzed the proliferation and differentiation capacities of the generated iPSCs using single cell NGS-based 24-chromosome aneuploidy screening and RNA sequencing. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 76 publications
2
9
0
Order By: Relevance
“…Given that differentiation capacity into HPCs of USC-iPSC is lower than that of PBMC-iPSCs, 3,2 -DHF and 3,4 -DHF treatment could be utilized to overcome the limitation of USC-iPSC's differentiation capacity into HPCs. We also observed that flavonoid enhanced the population of CD34+/CD45+ cells in PBMC-iPSC [43]. Overall, these data suggest that flavonoids, 3,2 -DHF and 3,4 -DHF could possibly facilitate the efficient use of USCs by enhancing the efficiencies of USC isolation and differentiation of USC-iPSCs into HPCs and further into hematopoietic lineage cells.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Given that differentiation capacity into HPCs of USC-iPSC is lower than that of PBMC-iPSCs, 3,2 -DHF and 3,4 -DHF treatment could be utilized to overcome the limitation of USC-iPSC's differentiation capacity into HPCs. We also observed that flavonoid enhanced the population of CD34+/CD45+ cells in PBMC-iPSC [43]. Overall, these data suggest that flavonoids, 3,2 -DHF and 3,4 -DHF could possibly facilitate the efficient use of USCs by enhancing the efficiencies of USC isolation and differentiation of USC-iPSCs into HPCs and further into hematopoietic lineage cells.…”
Section: Discussionsupporting
confidence: 57%
“…Human dermal fibroblasts (HDFs) with passage 5, adipose-derived stem cells (ADSC) with passage 1, and Wharton's jelly-derived MSCs (WJ-MSCs) with passage 2 were obtained from Cell2in (Seoul, Republic of Korea) (IRB 7001355-201507-BR-181). The human peripheral blood mononuclear cells (PBMCs) were prepared from the blood of healthy donors using density gradient centrifugation via Ficoll-Paque PLUS (GE Healthcare, Chicago, IL, USA) (IRB 7001355-201507-BR-072) as we described [43]. Basically, the USCs isolation from human urine samples were carried out based on the previously established protocol [44].…”
Section: Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we devised an improved protocol for the isolation of urine-derived stem cells and their further differentiation into immune cells ( 95 ). Moreover, our research group promoted the hematopoietic differentiation of hiPSCs using a novel small molecule ( 96 ). At the advent of COVID-19, it has become mandatory to discover therapeutic strategies that are easily reproducible and cost effective.…”
Section: Future Directionsmentioning
confidence: 99%
“…29 It protects cells against oxidative damage, 30,31 and is currently studied for its ability to improve the preparation and isolation of stem cells for regenerative medicine applications. [32][33][34] Its crystal structure has been characterized, using X-rays, 35 and its mass spectrum recorded. 36 2 0 3HF is a good candidate of study, as it is a simple 3HF derivative, but has shown to behave quite differently from other avonols.…”
Section: Introductionmentioning
confidence: 99%